Morphometric Analysis of Maxillary Central Incisor to Determine its Crown Form: A Model-based Cross-sectional Study - Jayasankar Purushothaman Pillai; Riddhi Patel; Alka Banker; J Rajarajeswari; Sukhdev Mishra (Wolters Kluwer Medknow Publications, 2016)
The size and shape of tooth crowns are morphogenetically predetermined during embryogenesis. The maxillary central incisors have contributed to sexual dimorphism, and several classifications of the form of maxillary central incisors are available in the literature. We, in the present study, aimed to analyze the mesiodistal (MD) measurements at two levels of maxillary central incisor, to determine its crown form. The study was conducted on 100 dental plaster models (50 males and 50 females). The MD dimensions at the contact area level MD_incisal (MD_I) and at the gingival papilla level (MD_G) and the gingivo-incisal height of the crown were measured in the dental models using digital Vernier caliper. The data were analyzed using SPSS version 16 statistical software. The mean values of all the three parameters measured were slightly greater for males and also for the left central incisors. There were no significant differences in all the three variables when the right and left incisors were compared. Significant differences were noted when the parameters are compared between genders. The height/width ratio of crown showed a significant difference between male and female. The value of the ratio between the two MD dimensions (MD_I and MD_G) was used to determine the crown form. The ratio between the MD dimensions at incisal and gingival area showed a significant difference between genders and no such significance was found between right and left central incisors. There is a significant difference in the form of maxillary central incisors between male and female samples and not between right and left. The MD dimensions at incisal and gingival thirds decide the form of crown.